ANALISIS PENGGUNAAN TENAGA FREELANCE PADA USAHA CATERING KOTA PEKANBARU (STUDI KASUS TENAGA FREELANCE PADA CV. BALEBAT) - Salsabila, Aisha; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is motivated by the use of freelancers at CV.Balebat in Pekanbaru City. Based on the survey results there are several obstacles that arise in the use of freelancers at CV.Balebat. The object of this study is to analyze the use of freelance personnel used at CV.Balebat and to Know and analyze the factors that affecting to CV.Balebat in using of freelance by adopting the theory of human resource effectiveness from Richard M Steers. The method used in this research is descriptive qualitative method. Based on the results of research that there are still some shortcomings and obstacles in the use of freelance workers at catering business of CV.Balebat Pekanbaru which certainly needs to be considered in order to improve service to consumers. Keywords: Freelance, tenaga kerja lepas, effectiveness